Increased variability in reaction time is associated with amyloid beta pathology at age 70 - Lu, Kirsty; Nicholas, Jennifer M.; James, Sarah‐Naomi; Lane, Christopher A.; Parker, Thomas D.; Keshavan, Ashvini; Keuss, Sarah E.; Buchanan, Sarah M.; Murray‐Smith, Heidi; Cash, David M.; Sudre, Carole H.; Malone, Ian B.; et al. (Alzheimer's & dementia : diagnosis, assessment & disease monitoring, 2020)
Introduction We investigated whether life‐course factors and neuroimaging biomarkers of Alzheimer's disease pathology predict reaction time (RT) performance in older adults. Methods Insight 46 study participants, all born in the same week in 1946 (n = 501; ages at assessment = 69 to 71 years), completed a 2‐choice RT task and amyloid beta (Aβ) positron emission tomography and MR imaging. We tested for associations between task outcomes (RT; error rate; intra‐individual variability in RT) and life‐course predictors including childhood cognitive ability and education. In a subsample of 406 cognitively normal participants, we investigated associations between task outcomes and biomarkers including Aβ‐positivity. Results Cognitively normal Aβ‐positive participants had 10% more variable RTs than Aβ‐negative participants, despite having similar mean RTs. Childhood cognitive ability and education independently predicted task performance. Discussion This study provides novel evidence that Aβ pathology is associated with poorer consistency of RT in cognitively normal older adults, at an age when dementia prevalence is still very low.